The Urgency Of The Establishment Of A World Mediation Body At The United Nations (PBB) - Sabela Gayo (International Asia Of Law and Money Laundering (IAML), 2026)
The dynamics of contemporary international conflicts point to the significant limitations of the United Nations mediation mechanism sourced from a Security Council structure with a veto system. This study analyzes the urgency of the establishment of a World mediation body as an institutional solution to the structural paralysis of the United Nations in carrying out the conflict mediation function for the period 2021-2025. Using normative legal research methods with an analysis of Law No. 37 of 1999, Law No. 24 of 2000, and Law No. 1 of 1982, the study found that the politicization of the mediation process by permanent members of the Security Council has reduced the credibility and effectiveness of the United Nations in resolving the Gaza conflict, Ukraine, and other humanitarian crises. The creation of a World mediation body is supported by the theory of institutional liberalism and empirical evidence of the success of neutral and professional international mediation. Optimal institutional design includes a representative membership structure, responsive operational procedures, diversified financing, and a comprehensive legal mandate independent of the Security Council. The implications of the establishment of this body include the diversification of dispute resolution channels, the strengthening of the role of the General Assembly, and the democratization of global governance through an inclusive redistribution of power, in line with the principles of Indonesia's active free foreign policy and commitment to World Peace.